2013
DOI: 10.1002/mrm.24950
|View full text |Cite
|
Sign up to set email alerts
|

Spatial encoding using the nonlinear field perturbations from magnetic materials

Abstract: This study shows the technical feasibility of using magnetic markers to produce encoding fields. Magnetic materials will allow generating spatial encoding fields, which can be tailored to an imaging application with less complexity and at lower cost compared to the use of gradient inserts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In order to simultaneously measure the location and orientation of the tracking device, a library of projections was built from simulated projections where the device was placed at the center of the field of view (FOV) and at various angles with respect to main field. These simulations were performed using a method described in Karimi et al .…”
Section: Methodsmentioning
confidence: 99%
“…In order to simultaneously measure the location and orientation of the tracking device, a library of projections was built from simulated projections where the device was placed at the center of the field of view (FOV) and at various angles with respect to main field. These simulations were performed using a method described in Karimi et al .…”
Section: Methodsmentioning
confidence: 99%
“…Effectively, a metallic implant creates a nonlinear and multidimensional frequency encoding of the surrounding spins because of its inherent susceptibility. Although this encoding concept is a novel concept in metal imaging, nonmetal work has shown that nonlinear and multidimensional gradient fields can be used for spatial encoding . In this work, we propose to exploit these spatial sensitivities using an “off‐resonance encoding” (ORE) strategy to accelerate acquisitions in the presence of metal.…”
Section: Theorymentioning
confidence: 99%